You can take a person out of the military, but you can’t take the military out of the person: findings from a ten-year identity study on transition from military to civilian life - Grimell, Jan (Frontiers in Sociology, 2024)
This article takes its starting point in a longitudinal interview study that began in 2013 with the aim of investigating identity reconstruction during the transition from military to civilian life. Annual follow-up interviews were conducted for 3 years, after which there was a break for 7 years until 2023 when a new interview cycle was conducted. The article presents the findings from this interview round. The purpose of the study was to describe the ways in which military identity had impacted the selves and lives of the participants. An inductive approach was employed in the analysis and an abductive approach used in the interpretative phase. The results showed, among other things, that a military identity, containing a particularly strong work ethic, had grown salient over the years. This military identity salience amplified the perception of a contrasting civilian work ethic, which generated moral frustration and even conflict. It was seen as imperative to maintain consistency between a military work ethic and the identity standard as a civilian employee rather than to modify the behavior to another standard, i.e., a civilian standard. These results were counterintuitive given the earlier interview cycles. A military work ethic was generally a powerful asset but could have negative health outcomes, manifesting as burnout. The results reflect the challenges in operating multiple identities tailored to contrasting moral regimes. Future longitudinal qualitative and quantitative research approaches to self-identity work among former service members are warranted.